Exon Domesday : méthodes numériques appliquées à la codicologie pour l’étude d’un manuscrit anglo-normand - Peter A. Stokes; Geoffroy Noël (Tabularia)
In this article, we present a methodological discussion of a study of the Exon Domesday Book, Exeter, Cathedral Library, ms 3500. Exon Domesday contains records for the south-west of England which were compiled for the Domesday survey and then reworked into Great Domesday Book as we know it today. Exon Domesday therefore provides a unique view into the workings of the early Anglo-Normans, providing us with crucial evidence of what they did, how and probably also why. However, the manuscript is extremely complex, being the work of a team of scribes working together under significant pressures of time. It is very irregular in composition, with quires ranging from one bifolium or even a singleton to those of twenty leaves. In order to understand the manuscript and its production, we have developed digital tools and approaches to help visualise and analyse the structure. Although they are based firmly in the research questions of the project, they are also founded on principles of codicology that we believe are applicable much more widely than just this project.